2020
DOI: 10.3389/fnbeh.2020.587715
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Plasma CircRNA-089763 and Postoperative Cognitive Dysfunction in Elderly Patients Undergoing Non-cardiac Surgery

Abstract: In our previous experiment, we found that there were abnormal levels of circRNA-089763 in the plasma exosomes of patients with postoperative cognitive dysfunction (POCD) after cardiac surgery. Therefore, the aim of this study was to further investigate the relationship between plasma circRNA-089763 level and POCD in elderly patients after non-cardiac surgery. A prospective cohort study was conducted to select elderly patients undergoing elective non-cardiac surgery. A total of 72 patients were enrolled in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…Blood loss, including postoperative oozing, as reflected by reduced hemoglobin levels, might render a patient susceptible to a higher risk of POCD in the present study. The conclusion that the occurrence of cognitive dysfunction is affected by intraoperative blood loss in elderly patients has consistently been confirmed [21,22]. A deficiency in oxygen supply to the brain may result in cognitive dysfunction, which may explain the association between low hemoglobin levels and POCD [23].…”
Section: Discussionmentioning
confidence: 89%
“…Blood loss, including postoperative oozing, as reflected by reduced hemoglobin levels, might render a patient susceptible to a higher risk of POCD in the present study. The conclusion that the occurrence of cognitive dysfunction is affected by intraoperative blood loss in elderly patients has consistently been confirmed [21,22]. A deficiency in oxygen supply to the brain may result in cognitive dysfunction, which may explain the association between low hemoglobin levels and POCD [23].…”
Section: Discussionmentioning
confidence: 89%
“…To name one landmark study included in the meta-analysis, the International Study of Post-Operative Cognitive Dysfunction (ISPOCD 1), found that among 1011 older surgical patients recruited in eight European countries and the USA, patients with more than a high school education had even a halved risk of POCD at one week after surgery compared with patients with less than high school education ( Moller et al 1998 ). Studies from various European and Asian countries and the USA that were not included in the 2017 meta-analysis ( Grichnik et al 1999 ) or published thereafter ( Bendikaite and Vimantaite 2020 ; Ehsani et al 2020 ; Huang et al 2020a ; Klinger et al 2019 ; Li et al 2020 ; Wang et al 2018 ; Yuhe et al 2020 ; Zhang et al 2019 ; Zhou et al 2020 ) too, consistently indicate that patients with a lower educational level are at increased POCD risk at discharge ( Zhang et al 2019 ) within days of surgery ( Ehsani et al 2020 ; Li et al 2020 ; Zhao et al 2020 ; Zhou et al 2020 ) but also during six to 12 weeks after surgery ( Grichnik et al 1999 ; Yuhe et al 2020 ). The fact that observations extend to several months after surgery is important because studies on POCD with longer follow-up periods offer preferred scope for conclusions: during shorter follow-up periods immediate effects of surgery on brain function including a potential influence of POD can prevail.…”
Section: Cognitive Epidemiology In a Surgical Settingmentioning
confidence: 99%
“…24 While cognitive function of POCD patients with higher levels of hsa-miR-572 in the peripheral blood was not recovered after surgery, 27 higher levels of plasma hsa-circR-089763 were related to the incidence of POCD in elderly patients undergoing noncardiac surgery. 41 3.5. ncRNAs as for Mechanisms of POCD. The novel mechanisms in terms of classical "circRNA/lncRNA− miRNA−mRNA" axes including lncRNA HOTAIR-Bdnf, 40 circ-Shank3-miR-3569-Fkbp5/Lrrc32, 29 and miR-206-IGF-1 30 were involved in the development of POCD.…”
Section: Differentially Expressed Ncrnas Inmentioning
confidence: 99%